A NEW METHOD FOR IN SITU ANALYSIS OF CARBON DIOXIDE ABSORPTION IN AQUEOUS MONOETHANOLAMINE BY RAMAN SPECTROSCOPY - WONG , MEE KEE (2017)
Aqueous phase characterization and thermodynamic modeling are important for designing and operating C02 capture systems, thus accurate determination of equilibrium of C02 in aqueous amine is of major interest. Many studies have been conducted on vapor liquid equilibria based on pressure change, but analysis on the liquid phase speciation is relatively scarce.